Padronização de um modelo murino e avaliação do papel do receptor CCR2 na doença periodontal experimental induzida por Porphyromonas gingivalis - Thales Augusto Anestino (2020)
Periodontal disease (PD) is an infectious inflammatory process that affects the teeth supporting tissues. One of the microorganisms associated with PD is Porphyromonas gingivalis, Gram-negative obligate anaerobic coccobacillus resident in the subgingival biofilm and classified as keystone-pathogen of chronic periodontitis. This bacterium promotes and maintains a dysbiosis of the dental subgingival biofilm. Thus, in response to dysbiosis, inflammatory osteoclastogenics mediators are produced, triggering the resorption of the alveolar bone. Among the inflammatory mediators produced in PD is CC chemokine ligand 2 (CCL2). When interacting with the chemokine type 2 receptor CC (CCR2), CCL2 promotes increased recruitment of macrophages to the site of infection, which may differentiate into osteoclasts. Thus, this study aims to standardize a murine model of PD induced by P. gingivalis and to evaluate the role of CCR2 in this process. To that end, mice were submitted to different protocols of periodontal infection (antimicrobial in drinking water, topical application of 0.12% chlorhexidine gel or no manipulation of the microbiota), being inoculated with 108 CFU / mL of P. gingivalis in the oral cavity. After 45 days, mice were euthanized, periodontal tissues were collected and processed for analysis of alveolar bone loss. Subsequently, infection kinetics was performed to assess the inflammatory response. Periodontal tissues were collected and processed for analysis. To evaluate the role of CCR2, groups of WT and Ccr2- / - mice were inoculated, and after 30 or 45 days the animals were euthanized, the periodontal tissues were collected and processed for further analysis. WT infected mice showed significant alveolar bone regardless adopted protocol. This alveolar bone loss is associated with an increased IL-6, osteoclasts and decreased CXCL-1, neutrophils and NAG production. Ccr 2-/- infected mice showed increased reactivity front the bacterial stimulus to showed a more phagocytic index in vitro and response assembly in acute phase to lead a greater alveolar bone loss in cronic phase, associated with an increased IL-1b, CCL2 and decreased IL-10 production when compared to WT infected mice. These results show that infection with P. gingivalis induces IL-6-associated bone resorption, as well as pointing out that CCR2 is important in bone remodeling associated with experimental PD. Keywords: Periodontal disease. Porphyromonas gingivalis. Chemokines. CCL2.